Electrolyte additive composition for lithium ion batteries, electrolyte containing said additive composition, and use of the electrolyte
Patent Information
- Application Number
- JP2024552260
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-16
- Filing Date
- 2023-07-19
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2043-07-19
Smart Images

Figure 2025506987000001_ABST
Abstract
Description
[Technical field]
[0001] The present application relates to the field of lithium ion batteries, and more particularly to an electrolyte additive composition for lithium ion batteries, an electrolyte including the additive composition, and applications of the electrolyte. [Background technology]
[0002] Lithium ion batteries have a higher energy density, a higher voltage, and a longer cycle life than traditional secondary batteries, and also have the advantages of being environmentally friendly, so that lithium ion batteries are widely used in many fields, such as notebook computers, mobile phones, digital products, electric vehicles, etc.
[0003] One important component of lithium ions is the electrolyte, and the role of the electrolyte is to transfer lithium ions between the positive and negative electrodes of the battery. The electrolyte usually includes a lithium salt electrolyte, an organic solvent, and an additive composition. The introduction of the additive composition can improve the battery's multiplication performance and cycle life, and reduce the impedance of the battery. Vinylene carbonate and vinylethylene carbonate are common film-forming additive compositions. Vinylene carbonate and vinylethylene carbonate generate electrochemical polymerization on the negative electrode surface to form a single layer of dense solid electrolyte film, which prevents the contact between the electrode material and the electrolyte, thereby preventing the electrolyte from generating further reduction decomposition on the negative electrode surface and suppressing side reactions between the electrolyte and the electrode material. At the same time, the solid electrolyte film can also prevent the solvent and lithium ions from being embedded together in the electrode material.
[0004] Power batteries are power sources for providing power sources to tools, and require sufficient film-forming additive composition to ensure sufficient cycling stability of the battery, but the increased amount of film-forming additive composition increases the cost and increases the impedance of the battery, and the battery's multiplication performance and low-temperature performance are all affected by the increased battery impedance. In addition, when the amount of additive composition such as vinylene carbonate is increased, the lithium ion battery using lithium nickel cobalt manganese oxide as the positive electrode material will obviously expand when operated at high temperatures, which is a safety hazard.
[0005] Therefore, how to research additive compositions so as to provide lithium ion batteries with low impedance, high cycle life, and excellent high and low temperature performance is an important issue in the field of lithium ion batteries. Summary of the Invention
[0006] In order to provide a lithium ion battery with low impedance, high cycle life, and excellent high and low temperature performance, the present application provides an electrolyte additive composition for a lithium ion battery, an electrolyte containing the additive composition, and uses of the electrolyte.
[0007] In a first aspect, the present application provides an electrolyte additive composition for a lithium ion battery, which uses the following technical solution:
[0008] An electrolyte additive composition for a lithium ion battery, comprising an unsaturated cyclic carbonate ester and an unsaturated chain carbonate ester, The unsaturated cyclic carbonate contains at least one of the following compounds: JPEG2025506987000002.jpg33135 The general structural formula of the unsaturated chain carbonate ester is as follows: JPEG2025506987000003.jpg2060Here, R1 is a hydrocarbon group or a fluorinated hydrocarbon group containing 1 to 6 carbon atoms, R2 is a hydrocarbon group or a fluorinated hydrocarbon group containing 1 to 6 carbon atoms, and the A group is an avinylene group or an avinyl group.
[0009] In a specific embodiment, the unsaturated chain carbonate ester is at least one of the following compounds: JPEG2025506987000004.jpg10372 JPEG2025506987000005.jpg14168
[0010] In one specific embodiment, the mass ratio of the unsaturated cyclic carbonate to the unsaturated chain carbonate is (0.5 to 5):(0.05 to 10).
[0011] In a second aspect, the present application provides a lithium-ion battery electrolyte using the following technical solution:
[0012] The lithium ion battery electrolyte includes a lithium salt electrolyte, an organic solvent, and an additive composition.
[0013] In one specific embodiment, the mass ratio of the unsaturated cyclic carbonate ester in the additive composition to the electrolyte is 0.5% to 5%, and the mass ratio of the unsaturated chain carbonate ester in the additive composition to the electrolyte is 0.05% to 10%.
[0014] In a specific embodiment, the organic solvent is at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethylene carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl butyl carbonate, propylene carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, difluoroethyl acetate, trifluoroethyl acetate, trifluoroethyl methyl carbonate, and bistrifluoroethyl carbonate.
[0015] In a specific embodiment, the lithium salt electrolyte is at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorophosphate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonimide, lithium bis(trifluoromethanesulfonyl)imide, lithium bioxalate borate, lithium difluorooxalate borate, lithium tetrafluorooxalate phosphate, lithium difluorobisoxalate phosphate, and lithium fluorosulfonyl(trifluoromethylsulfonyl)imide. Here, the molar concentration of the electrolyte in the electrolytic solution is 0.5 to 2 mol / L.
[0016] The lithium ion battery electrolyte provided in the present application is applicable to lithium ion batteries using lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminate, lithium iron manganese phosphate, or lithium nickel cobalt manganese aluminate as the positive electrode.
[0017] In a specific embodiment, the lithium ion battery electrolyte provided in the present application is applied to a lithium ion battery having a negative electrode made of a carbon material or a silicon-based material.
[0018] In summary, the present application has the following beneficial effects: The present application provides a mixture of unsaturated cyclic carbonate and unsaturated chain carbonate as an additive composition for a lithium ion battery electrolyte, which, at an appropriate ratio, can provide the lithium ion battery with low impedance, excellent cycle performance, especially low-temperature cycle performance, and can suppress swelling caused by electrolyte decomposition and improve the battery's high-temperature cycle and high-temperature storage performance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present application will now be described in more detail with reference to examples. Working Example
[0020] In an embodiment of the present application, an electrolyte for a lithium ion battery is provided.
[0021] The method for producing the electrolyte includes the following steps.
[0022] Step 1: In a glove box filled with nitrogen or argon, the water and oxygen contents in the glove box are both ≦0.1 ppm, and the organic solvent and the lithium salt electrolyte are mixed uniformly to obtain a basic electrolyte solution.
[0023] Step 2: In the glove box still filled with nitrogen or argon, the water and oxygen contents in the glove box are both ≦0.1 ppm. Add the additive composition to the basic electrolyte and mix uniformly to obtain the electrolyte.
[0024] The additive composition in this embodiment is a mixture of an unsaturated cyclic carbonate and an unsaturated chain carbonate.
[0025] The unsaturated cyclic carbonate in this embodiment is selected from the following compounds. JPEG2025506987000006.jpg33130
[0026] In this embodiment, the general structural formula of the unsaturated chain carbonate ester is as follows: JPEG2025506987000007.jpg2060Here, R1 is a hydrocarbon group or a fluorinated hydrocarbon group containing 1 to 6 carbon atoms, R2 is a hydrocarbon group or a fluorinated hydrocarbon group containing 1 to 6 carbon atoms, and the A group is an avinylene group or an avinyl group.
[0027] Specifically, the unsaturated chain carbonate ester in this embodiment is selected from the following compounds: JPEG2025506987000008.jpg13275 JPEG2025506987000009.jpg11368
[0028] In this embodiment, the organic solvent is selected from at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethylene carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl butyl carbonate, propylene carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, difluoroethyl acetate, trifluoroethyl acetate, trifluoroethyl methyl carbonate, and bistrifluoroethyl carbonate.
[0029] Preferably, the organic solvent in this embodiment is a mixture of ethylene carbonate, methyl ethyl carbonate and dimethyl carbonate, and the volume ratio of ethylene carbonate, methyl ethyl carbonate and dimethyl carbonate is 1:1:1.
[0030] In this embodiment, the lithium salt electrolyte is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorophosphate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonimide, lithium bis(trifluoromethanesulfonyl)imide, lithium bioxalate borate, lithium difluorooxalate borate, lithium tetrafluorooxalate phosphate, lithium difluorobisoxalate phosphate, and lithium fluorosulfonyl(trifluoromethylsulfonyl)imide. Here, the molar concentration of the electrolyte in the electrolytic solution is 0.5-2 mol / L.
[0031] Preferably, the lithium salt electrolyte in this embodiment is lithium hexafluorophosphate, and the molar concentration of lithium hexafluorophosphate is 1 mol / L.
[0032] This embodiment further provides a method for manufacturing a lithium ion battery, which includes the following steps:
[0033] In a glove box filled with nitrogen or argon, both of which have a water and oxygen content of ≦0.1 ppm, the electrolyte prepared in each example and comparative example was dissolved in LiFePO4 or LiNi 0.5 Co 0.2 Mn 0.3 Inject O2 into a lithium-ion battery cell with a positive electrode material and artificial graphite as the negative electrode. After injection is complete, the cell is sealed and left to stand, then formed, aged, resealed, and divided to obtain a lithium-ion battery.
[0034] This embodiment further provides a method for detecting lithium ion battery performance, including the following detection method.
[0035] (1) Test method for room temperature direct current impedance (DCIR) of lithium-ion batteries. The specific process for lithium-ion batteries using LiFePO4 as the positive electrode material is as follows:
[0036] At 25℃, charge the formed battery to 3.65V at 1C constant current and constant voltage, set the cut-off current to 0.05C, and discharge to 2V at 1C constant current, and record the discharge capacity Qt. Charge to 3.65V at 1C constant current and constant voltage, fully charge at a cut-off current of 0.05C, and then discharge 50% Qt of capacity at 1C constant current. Leave it for 1 hour, record the voltage V1 after leaving it, discharge it at a constant current of 5Qt for 10 seconds, and record the voltage V2 after discharge. Discharge DC impedance (DCIR) = (V1-V2) / (5 x Qt).
[0037] LiNi 0.5 Co 0.2 Mn 0.3 The specific process for a lithium-ion battery using O2 as the positive electrode material is as follows:
[0038] At 25℃, charge the formed battery to 4.35V at 1C constant current and constant voltage, set the cut-off current to 0.05C, and discharge to 3V at 1C constant current, and record the discharge capacity Qt. Charge to 4.35V at 1C constant current and constant voltage, fully charge at a cut-off current of 0.05C, and then discharge 50% Qt of capacity at 1C constant current. Leave it for 1 hour, record the voltage V3 after leaving it, and discharge it at a constant current of 5Qt for 10 seconds, and record the voltage V4 after discharge. Discharge DC impedance (DCIR) = (V3-V4) / (5 x Qt).
[0039] (2) Test method for lithium-ion battery cycle performance. The specific process for lithium-ion batteries using LiFePO4 as the positive electrode material is as follows:
[0040] a. At 25℃, charge the formed battery to 3.65V at 1C constant current and constant voltage, set the cutoff current to 0.05C, and then discharge to 2V at 1C constant current. After 500 charge / discharge cycles, calculate the discharge capacity retention rate after the 500th cycle. Discharge capacity retention rate (%) at 25°C = discharge capacity after 500th cycle / discharge capacity after first cycle × 100%
[0041] b. At 0°C, charge the formed battery to 3.65V at a constant current and voltage of 1C, set the cut-off current to 0.05C, and then discharge to 2V at a constant current of 1C. After 80 charge / discharge cycles, calculate the discharge capacity retention rate after the 80th cycle. Discharge capacity retention rate (%) at 0° C.=discharge capacity after 80th cycle / discharge capacity after first cycle×100%.
[0042] LiNi 0.5 Co 0.2 Mn 0.3 The specific process for a lithium-ion battery using O2 as the positive electrode material is as follows:
[0043] a. At 25℃, charge the formed battery to 4.35V at 1C constant current and constant voltage, set the cutoff current to 0.05C, and then discharge to 3V at 1C constant current. After 800 charge / discharge cycles, calculate the discharge capacity retention rate after the 800th cycle. Discharge capacity retention rate (%) at 25°C = discharge capacity after 800th cycle / discharge capacity after first cycle × 100%
[0044] b. At 45℃, charge the formed battery to 4.35V at 1C constant current and constant voltage, set the cut-off current to 0.05C, and then discharge to 3V at 1C constant current. After 400 charge / discharge cycles, calculate the discharge capacity retention rate after the 400th cycle. Discharge capacity retention rate (%) at 45°C = discharge capacity after 400th cycle / discharge capacity after first cycle x 100%.
[0045] (3) Test method for high-temperature storage performance of lithium-ion batteries. The specific process for lithium-ion batteries using LiFePO4 as the positive electrode material is as follows:
[0046] At 25°C, charge the battery to 3.65V at a constant current and voltage of 0.5C, set the cut-off current to 0.05C, and discharge to 2V at a constant current of 0.5C, and record the discharge capacity, i.e., the initial discharge capacity. Then, charge to 3.65V at a constant current and voltage of 0.5C. Place the fully charged battery in a constant temperature environment of 60°C and store it for 7 days. After 7 days, take it out and leave it at 25°C for 4 hours. After the battery has cooled to room temperature, discharge to 2V at a constant current of 0.5C, and record the discharge capacity, i.e., the retention capacity. Charge to 3.65V at a constant current and voltage of 0.5C, set the cut-off current to 0.05C, and discharge to 2V at a constant current of 0.5C, and record the discharge capacity, i.e., the recovery capacity. Battery capacity maintenance rate (%) = maintenance capacity / initial capacity x 100% Battery capacity recovery rate (%) = recovery capacity / initial capacity x 100%.
[0047] LiNi 0.5 Co 0.2 Mn 0.3 The specific process for a lithium-ion battery using O2 as the positive electrode material is as follows:
[0048] At 25°C, charge the battery to 4.35V at a constant current and voltage of 0.5C, set the cutoff current to 0.05C, and discharge to 3V at a constant current of 0.5C, and record the discharge capacity, i.e., the initial discharge capacity. Then, charge to 4.35V at a constant current and voltage of 0.5C, and measure the initial battery thickness. Place the fully charged battery in a constant temperature environment of 60°C and store it for 7 days. After 7 days, remove it and leave it at 25°C for 4 hours. After the battery has cooled to room temperature, measure the battery thickness after storage. Discharge to 3V at a constant current of 0.5C, and record the discharge capacity, i.e., the retention capacity. Charge to 4.35V at a constant current and voltage of 0.5C, set the cutoff current to 0.05C, and discharge to 3V at a constant current of 0.5C, and record the discharge capacity, i.e., the recovery capacity. Battery capacity maintenance rate (%) = maintenance capacity / initial capacity x 100% Battery capacity recovery rate (%) = recovery capacity / initial capacity x 100% Thickness expansion rate (%) = (thickness after storage - initial thickness) / initial thickness × 100%.
[0049] The following will explain the present invention using specific examples. Example 1
[0050] The method for producing the electrolyte includes the following steps.
[0051] Step 1: in a glove box filled with nitrogen or argon, the water and oxygen contents in the glove box are all ≦0.1ppm, ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate are mixed uniformly to obtain an organic solvent mixture, the volume ratio of ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate is 1:1:1. Lithium hexafluorophosphate is added to the organic solvent mixture and mixed uniformly to obtain a basic electrolyte, the concentration of lithium hexafluorophosphate in the basic electrolyte is 1mol / L.
[0052] Step 2: In the glove box still filled with nitrogen or argon, the water and oxygen contents in the glove box are both ≦0.1 ppm. The unsaturated cyclic carbonate in the additive composition and the unsaturated linear carbonate in the additive composition are added to the basic electrolyte, and mixed uniformly to obtain the electrolyte.
[0053] Here, in Example 1, the unsaturated chain carbonate ester is a compound of formula (2-a), and the unsaturated cyclic carbonate ester is a compound of formula (1-a). In the final electrolyte solution, the mass percentage of the unsaturated chain carbonate ester is 1%, and the mass percentage of the unsaturated cyclic carbonate ester is 1%.
[0054] Example 1 further provides a method for producing a lithium ion battery, the method including the following steps:
[0055] In a glove box filled with nitrogen or argon, with water and oxygen contents both less than 0.1 ppm, the prepared electrolyte is injected into a lithium-ion battery cell with LiFePO4 as the positive electrode material and artificial graphite as the negative electrode. After the electrolyte injection is complete, the cell is sealed and left to stand, then formed, aged, resealed, and divided to obtain a lithium-ion battery.
[0056] Example 1 further provides a method for testing the room temperature direct current impedance (DCIR) of a lithium ion battery, the method including the following steps:
[0057] At 25℃, charge the formed battery to 3.65V at 1C constant current and constant voltage, set the cut-off current to 0.05C, and discharge to 2V at 1C constant current, and record the discharge capacity Qt. Charge to 3.65V at 1C constant current and constant voltage, fully charge at a cut-off current of 0.05C, and then discharge 50% Qt of capacity at 1C constant current. Leave it for 1 hour, record the voltage V1 after leaving it, discharge it at a constant current of 5Qt for 10 seconds, and record the voltage V2 after discharge. Discharge DC impedance (DCIR) = (V1-V2) / (5 x Qt). Examples 2 to 6 and Comparative Examples 1 to 4
[0058] The difference between Example 1 and Examples 2 to 6 and Comparative Examples 1 to 4 is that the additive composition in the battery electrolyte is different. The lithium ion batteries of Examples 2 to 6 and Comparative Examples 1 to 4 all use LiFePO4 as a positive electrode material, and the lithium ion battery performance test methods of Examples 2 to 6 and Comparative Examples 1 to 4 are all the same as those of Example 1.
[0059] Table 1 shows the additive composition formulations and the battery performance detection results for Examples 1 to 6 and Comparative Examples 1 to 4. Table 1: Additive composition blends and battery performance detection results for Examples 1 to 6 and Comparative Examples 1 to 4 JPEG2025506987000010.jpg131145Example 7
[0060] The method for producing the electrolyte includes the following steps.
[0061] Step 1: in a glove box filled with nitrogen or argon, the water and oxygen contents in the glove box are all ≦0.1ppm, ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate are mixed uniformly to obtain an organic solvent mixture, the volume ratio of ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate is 1:1:1. Lithium hexafluorophosphate is added to the organic solvent mixture and mixed uniformly to obtain a basic electrolyte, the concentration of lithium hexafluorophosphate in the basic electrolyte is 1mol / L.
[0062] Step 2: In the glove box still filled with nitrogen or argon, the water and oxygen contents in the glove box are both ≦0.1 ppm. The unsaturated cyclic carbonate in the additive composition and the unsaturated linear carbonate in the additive composition are added to the basic electrolyte, and mixed uniformly to obtain the electrolyte.
[0063] Here, in Example 7, the unsaturated chain carbonate is a compound of formula (2-b), and the unsaturated cyclic carbonate is a compound of formula (1-a). In the final electrolyte solution, the mass percentage of the unsaturated chain carbonate is 1%, and the mass percentage of the unsaturated cyclic carbonate is 1%.
[0064] Example 7 further provides a method for preparing a lithium ion battery, the method including the steps of:
[0065] The electrolyte prepared was dissolved in water and oxygen in a nitrogen or argon filled glove box with a water and oxygen content of ≦0.1 ppm. 0.5 Co 0.2 Mn 0.3 Inject O2 into a lithium-ion battery cell with a positive electrode material and artificial graphite as the negative electrode. After injection is complete, the cell is sealed and left to stand, then formed, aged, resealed, and divided to obtain a lithium-ion battery.
[0066] Example 7 further provides a method for testing the room temperature direct current impedance (DCIR) of a lithium ion battery, the method including the following steps:
[0067] At 25℃, charge the formed battery to 4.35V at 1C constant current and constant voltage, set the cut-off current to 0.05C, and discharge to 3V at 1C constant current, and record the discharge capacity Qt. Charge to 4.35V at 1C constant current and constant voltage, fully charge at a cut-off current of 0.05C, and then discharge 50% Qt of capacity at 1C constant current. Leave it for 1 hour, record the voltage V3 after leaving it, and discharge it at a constant current of 5Qt for 10 seconds, and record the voltage V4 after discharge. Discharge DC impedance (DCIR) = (V3-V4) / (5 x Qt). Examples 8 to 12 and Comparative Examples 5 to 8
[0068] The difference between Example 7 and Examples 8 to 12 and Comparative Examples 5 to 8 is that the additive composition in the battery electrolyte is different. 0.5 Co 0.2 Mn 0.3 O2 was used as the positive electrode material, and the lithium ion battery performance test methods of Examples 8 to 12 and Comparative Examples 5 to 8 were all the same as those of Example 7.
[0069] Table 2 shows the additive composition formulations and the battery performance detection results for Examples 7 to 12 and Comparative Examples 5 to 8. Table 2: Additive composition blends and battery performance detection results for Examples 7 to 12 and Comparative Examples 5 to 8 JPEG2025506987000011.jpg131145
[0070] As can be seen from the test results of Examples 1 to 12 and Comparative Examples 1 to 8 in Tables 1 and 2, when the electrolyte of the additive composition of the present application is used, the discharge DC impedance can be significantly lowered in both lithium iron phosphate batteries and nickel-cobalt-manganese ternary batteries than in the comparative examples using only the first component additive. Example 13
[0071] The method for producing the electrolyte includes the following steps.
[0072] Step 1: in a glove box filled with nitrogen or argon, the water and oxygen contents in the glove box are all ≦0.1ppm, ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate are mixed uniformly to obtain an organic solvent mixture, the volume ratio of ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate is 1:1:1. Lithium hexafluorophosphate is added to the organic solvent mixture and mixed uniformly to obtain a basic electrolyte, the concentration of lithium hexafluorophosphate in the basic electrolyte is 1mol / L.
[0073] Step 2: In the glove box still filled with nitrogen or argon, the water and oxygen contents in the glove box are both ≦0.1 ppm. The unsaturated cyclic carbonate in the additive composition and the unsaturated linear carbonate in the additive composition are added to the basic electrolyte, and mixed uniformly to obtain the electrolyte.
[0074] Here, in Example 13, the unsaturated chain carbonate is a compound of formula (2-b), and the unsaturated cyclic carbonate is a compound of formula (1-a). In the final electrolyte solution, the mass percentage of the unsaturated chain carbonate is 2%, and the mass percentage of the unsaturated cyclic carbonate is 1%.
[0075] Example 13 further provides a method for preparing a lithium ion battery, the method including the steps of:
[0076] In a glove box filled with nitrogen or argon, with water and oxygen contents both less than 0.1 ppm, the prepared electrolyte is injected into a lithium-ion battery cell with LiFePO4 as the positive electrode material and artificial graphite as the negative electrode. After the electrolyte injection is complete, the cell is sealed and left to stand, then formed, aged, resealed, and divided to obtain a lithium-ion battery.
[0077] Example 13 further provides a method for testing the cycling performance of a lithium-ion battery, the method including the following steps:
[0078] (1) At 25°C, charge the formed battery to 3.65 V at a constant current and voltage of 1 C, set the cutoff current to 0.05 C, and then discharge to 2 V at a constant current of 1 C. After 500 charge / discharge cycles, calculate the discharge capacity retention rate after the 500th cycle. Discharge capacity retention rate (%) at 25°C = discharge capacity after 500th cycle / discharge capacity after first cycle × 100%
[0079] (2) At 0°C, charge the formed battery to 3.65 V at a constant current and voltage of 1 C, set the cutoff current to 0.05 C, and then discharge to 2 V at a constant current of 1 C. After 80 charge / discharge cycles, calculate the discharge capacity retention rate after the 80th cycle. Discharge capacity retention rate (%) at 0° C.=discharge capacity after 80th cycle / discharge capacity after first cycle×100%. Examples 14 to 18 and Comparative Examples 9 to 12
[0080] The difference between Examples 14 to 18 and Comparative Examples 9 to 12 and Example 13 is that the additive composition in the battery electrolyte is different. The lithium ion batteries of Examples 14 to 18 and Comparative Examples 9 to 12 all use LiFePO4 as a positive electrode material, and the lithium ion battery performance test methods of Examples 14 to 18 and Comparative Examples 9 to 12 are all the same as those of Example 13.
[0081] Table 3 shows the additive composition formulations and the battery performance detection results for Examples 13 to 18 and Comparative Examples 9 to 12. Table 3: Additive composition blends and battery performance detection results for Examples 13 to 18 and Comparative Examples 9 to 12 JPEG2025506987000012.jpg139145Example 19
[0082] The method for producing the electrolyte includes the following steps.
[0083] Step 1: in a glove box filled with nitrogen or argon, the water and oxygen contents in the glove box are all ≦0.1ppm, ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate are mixed uniformly to obtain an organic solvent mixture, the volume ratio of ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate is 1:1:1. Lithium hexafluorophosphate is added to the organic solvent mixture and mixed uniformly to obtain a basic electrolyte, the concentration of lithium hexafluorophosphate in the basic electrolyte is 1mol / L.
[0084] Step 2: In the glove box still filled with nitrogen or argon, the water and oxygen contents in the glove box are both ≦0.1 ppm. The unsaturated cyclic carbonate in the additive composition and the unsaturated linear carbonate in the additive composition are added to the basic electrolyte, and mixed uniformly to obtain the electrolyte.
[0085] Here, in Example 19, the unsaturated chain carbonate is a compound of formula (2-a), and the unsaturated cyclic carbonate is a compound of formula (1-a). In the final electrolyte solution, the mass percentage of the unsaturated chain carbonate is 0.5%, and the mass percentage of the unsaturated cyclic carbonate is 1%.
[0086] Example 19 further provides a method for preparing a lithium ion battery, the method including the steps of:
[0087] The electrolyte prepared was dissolved in water and oxygen in a nitrogen or argon filled glove box with a water and oxygen content of ≦0.1 ppm. 0.5 Co 0.2 Mn 0.3 Inject O2 into a lithium-ion battery cell with a positive electrode material and artificial graphite as the negative electrode. After injection is complete, the cell is sealed and left to stand, then formed, aged, resealed, and divided to obtain a lithium-ion battery.
[0088] Example 19 further provides a method for testing the cycling performance of a lithium-ion battery, the method including the following steps:
[0089] (1) At 25°C, charge the formed battery to 4.35V at a constant current and voltage of 1C, set the cutoff current to 0.05C, and then discharge to 3V at a constant current of 1C. After 800 charge / discharge cycles, calculate the discharge capacity retention rate after the 800th cycle. Discharge capacity retention rate (%) at 25°C = discharge capacity after 800th cycle / discharge capacity after first cycle × 100%
[0090] (2) At 45°C, charge the formed battery to 4.35V at a constant current and voltage of 1C, set the cutoff current to 0.05C, and then discharge to 3V at a constant current of 1C. After 400 charge / discharge cycles, calculate the discharge capacity retention rate after the 400th cycle. Discharge capacity retention rate (%) at 45°C = discharge capacity after 400th cycle / discharge capacity after first cycle x 100%. Examples 20 to 24 and Comparative Examples 13 to 16
[0091] The difference between Examples 20 to 24 and Comparative Examples 13 to 16 and Example 19 is that the additive composition in the battery electrolyte is different. 0.5 Co 0.2 Mn 0.3 O2 was used as the positive electrode material, and the lithium ion battery performance test methods of Examples 20 to 24 and Comparative Examples 13 to 16 were all the same as those of Example 19.
[0092] Table 4 shows the additive composition formulations and the battery performance detection results for Examples 19 to 24 and Comparative Examples 13 to 16. Table 4. Additive composition formulations and battery performance tests for Examples 19 to 24 and Comparative Examples 13 to 16 Results table JPEG2025506987000013.jpg149145
[0093] As can be seen from the test results of Examples 13 to 24 and Comparative Examples 9 to 16 in Tables 3 and 4, the batteries using the electrolyte containing the additive composition provided in the present application have higher room temperature capacity retention rates than the comparative examples, both for the lithium iron phosphate batteries and for the nickel-cobalt-manganese ternary batteries. In the lithium iron phosphate batteries, the capacity retention rate at low temperatures is significantly improved compared to the comparative examples. In the nickel-cobalt-manganese ternary batteries, the high temperature capacity retention rate is also improved. Example 25
[0094] The method for producing the electrolyte includes the following steps.
[0095] Step 1: in a glove box filled with nitrogen or argon, the water and oxygen contents in the glove box are all ≦0.1ppm, ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate are mixed uniformly to obtain an organic solvent mixture, the volume ratio of ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate is 1:1:1. Lithium hexafluorophosphate is added to the organic solvent mixture and mixed uniformly to obtain a basic electrolyte, the concentration of lithium hexafluorophosphate in the basic electrolyte is 1mol / L.
[0096] Step 2: In the glove box still filled with nitrogen or argon, the water and oxygen contents in the glove box are both ≦0.1 ppm. The unsaturated cyclic carbonate in the additive composition and the unsaturated linear carbonate in the additive composition are added to the basic electrolyte, and mixed uniformly to obtain the electrolyte.
[0097] Here, in Example 25, the unsaturated chain carbonate ester is a compound of formula (2-a), and the unsaturated cyclic carbonate ester is a compound of formula (1-a). In the final electrolyte solution, the mass percentage of the unsaturated chain carbonate ester is 1%, and the mass percentage of the unsaturated cyclic carbonate ester is 1%.
[0098] Example 25 further provides a method for preparing a lithium ion battery, the method including the steps of:
[0099] In a glove box filled with nitrogen or argon, with water and oxygen contents both less than 0.1 ppm, the prepared electrolyte is injected into a lithium-ion battery cell with LiFePO4 as the positive electrode material and artificial graphite as the negative electrode. After the electrolyte injection is complete, the cell is sealed and left to stand, then formed, aged, resealed, and divided to obtain a lithium-ion battery.
[0100] Example 25 further provides a method for testing the high temperature storage performance of a lithium ion battery, the method including the following steps:
[0101] At 25°C, charge the battery to 3.65V at a constant current and voltage of 0.5C, set the cut-off current to 0.05C, and discharge to 2V at a constant current of 0.5C, and record the discharge capacity, i.e., the initial discharge capacity. Then, charge to 3.65V at a constant current and voltage of 0.5C. Place the fully charged battery in a constant temperature environment of 60°C and store it for 7 days. After 7 days, take it out and leave it at 25°C for 4 hours. After the battery has cooled to room temperature, discharge to 2V at a constant current of 0.5C, and record the discharge capacity, i.e., the retention capacity. Charge to 3.65V at a constant current and voltage of 0.5C, set the cut-off current to 0.05C, and discharge to 2V at a constant current of 0.5C, and record the discharge capacity, i.e., the recovery capacity. Battery capacity maintenance rate (%) = maintenance capacity / initial capacity x 100% Battery capacity recovery rate (%) = recovery capacity / initial capacity x 100%. Examples 26 to 30 and Comparative Examples 17 to 20
[0102] The difference between Examples 26-30 and Comparative Examples 17-20 and Example 25 is that the additive composition in the battery electrolyte is different. The lithium ion batteries of Examples 26-30 and Comparative Examples 17-20 all use LiFePO4 as a positive electrode material, and the lithium ion battery performance test methods of Examples 26-30 and Comparative Examples 17-20 are all the same as those of Example 26.
[0103] Table 5 shows the additive composition formulations and battery performance detection results for Examples 25 to 30 and Comparative Examples 17 to 20. Table 5: Additive composition blends and battery performance detection results for Examples 25 to 30 and Comparative Examples 17 to 20 JPEG2025506987000014.jpg139159 Example 31
[0104] The method for producing the electrolyte includes the following steps.
[0105] Step 1: in a glove box filled with nitrogen or argon, the water and oxygen contents in the glove box are all ≦0.1ppm, ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate are mixed uniformly to obtain an organic solvent mixture, the volume ratio of ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate is 1:1:1. Lithium hexafluorophosphate is added to the organic solvent mixture and mixed uniformly to obtain a basic electrolyte, the concentration of lithium hexafluorophosphate in the basic electrolyte is 1mol / L.
[0106] Step 2: In the glove box still filled with nitrogen or argon, the water and oxygen contents in the glove box are both ≦0.1 ppm. The unsaturated cyclic carbonate in the additive composition and the unsaturated linear carbonate in the additive composition are added to the basic electrolyte, and mixed uniformly to obtain the electrolyte.
[0107] Here, in Example 31, the unsaturated chain carbonate is a compound of formula (2-b), and the unsaturated cyclic carbonate is a compound of formula (1-a). In the final electrolyte solution, the mass percentage of the unsaturated chain carbonate is 1%, and the mass percentage of the unsaturated cyclic carbonate is 1%.
[0108] Example 31 further provides a method for preparing a lithium ion battery, the method including the steps of:
[0109] The electrolyte prepared was dissolved in water and oxygen in a nitrogen or argon filled glove box with a water and oxygen content of ≦0.1 ppm. 0.5 Co 0.2 Mn 0.3Inject O2 into a lithium-ion battery cell with a positive electrode material and artificial graphite as the negative electrode. After injection is complete, the cell is sealed and left to stand, then formed, aged, resealed, and divided to obtain a lithium-ion battery.
[0110] Example 31 further provides a method for testing the high temperature storage performance of a lithium ion battery, the method including the following steps:
[0111] At 25°C, charge the battery to 4.35V at a constant current and voltage of 0.5C, set the cutoff current to 0.05C, and discharge to 3V at a constant current of 0.5C, and record the discharge capacity, i.e., the initial discharge capacity. Then, charge to 4.35V at a constant current and voltage of 0.5C, and measure the initial battery thickness. Place the fully charged battery in a constant temperature environment of 60°C and store it for 7 days. After 7 days, remove it and leave it at 25°C for 4 hours. After the battery has cooled to room temperature, measure the battery thickness after storage. Discharge to 3V at a constant current of 0.5C, and record the discharge capacity, i.e., the retention capacity. Charge to 4.35V at a constant current and voltage of 0.5C, set the cutoff current to 0.05C, and discharge to 3V at a constant current of 0.5C, and record the discharge capacity, i.e., the recovery capacity. Battery capacity maintenance rate (%) = maintenance capacity / initial capacity x 100% Battery capacity recovery rate (%) = recovery capacity / initial capacity x 100% Thickness expansion rate (%) = (thickness after storage - initial thickness) / initial thickness × 100%. Examples 32 to 36 and Comparative Examples 21 to 24
[0112] The difference between Examples 32 to 36 and Comparative Examples 21 to 24 and Example 31 is that the additive composition in the battery electrolyte is different. 0.5 Co 0.2 Mn 0.3 O2 was used as the positive electrode material, and the lithium ion battery performance test methods of Examples 32 to 36 and Comparative Examples 21 to 24 were all the same as those of Example 31.
[0113] Table 6 shows the additive composition formulations and the battery performance detection results for Examples 31 to 36 and Comparative Examples 21 to 24. Table 6: Additive composition blends and battery performance detection results for Examples 31 to 36 and Comparative Examples 21 to 24 JPEG2025506987000015.jpg138154
[0114] As can be seen from the test results of Examples 25 to 36 and Comparative Examples 17 to 24 in Tables 5 and 6, the capacity retention rate and capacity recovery rate after high-temperature storage of the comparative examples are not very good. However, for the batteries using the electrolyte containing the additive composition provided in the present application, whether the positive electrode material is lithium iron phosphate or a nickel-cobalt-manganese ternary system, the high-temperature storage performance is improved and the expansion after high-temperature storage is also suppressed.
[0115] In short, in this application, an unsaturated cyclic carbonate and an unsaturated chain carbonate are used as an additive composition in a lithium ion battery electrolyte, and the additive composition is used in an appropriate ratio to provide the lithium ion battery with low impedance and excellent cycle performance, especially low temperature cycle performance, and can suppress swelling caused by electrolyte decomposition and improve the battery's high temperature cycle and high temperature storage performance.
[0116] The specific examples are merely illustrative of the present application and do not limit the present application. After reading this specification, a person skilled in the art may make amendments to the present examples as necessary without making any creative contribution thereto, but as long as they are within the scope of the claims of this application, they shall be protected by the Patent Law.
Claims
1. 1. An electrolyte additive composition for a lithium ion battery, comprising: The unsaturated cyclic carbonate ester and the unsaturated chain carbonate ester are included. The unsaturated cyclic carbonate contains at least one of the following compounds: The general structural formula of the unsaturated chain carbonate ester is as follows: Here, R 1 is a hydrocarbon group or a fluorinated hydrocarbon group containing 1 to 6 carbon atoms, R 2 is a hydrocarbon or fluorinated hydrocarbon group containing 1 to 6 carbon atoms, and the A group is an avinylene group or an avinyl group.
1. An electrolyte additive composition for a lithium ion battery.
2. The unsaturated chain carbonate ester is at least one of the following compounds:
2. The electrolyte additive composition for a lithium ion battery according to claim 1 .
3. The mass ratio of the unsaturated cyclic carbonate ester to the unsaturated chain carbonate ester is (0.5 to 5):(0.05 to 10).
2. The electrolyte additive composition for lithium ion batteries according to claim 1.
4. 1. A lithium ion battery electrolyte comprising: A lithium salt electrolyte, an organic solvent, and the additive composition according to any one of claims 1 to 3. A lithium ion battery electrolyte comprising:
5. The mass ratio of the unsaturated cyclic carbonate ester in the additive composition to the electrolyte is 0.5% to 5%, and the mass ratio of the unsaturated chain carbonate ester in the additive composition to the electrolyte is 0.05% to 10%.
5. The lithium ion battery electrolyte according to claim 4.
6. The organic solvent is at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethylene carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl butyl carbonate, propylene carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, difluoroethyl acetate, trifluoroethyl acetate, trifluoroethyl methyl carbonate, and bistrifluoroethyl carbonate.
5. The lithium ion battery electrolyte according to claim 4.
7. The lithium salt electrolyte is at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorophosphate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonimide, lithium bis(trifluoromethanesulfonyl)imide, lithium bioxalate borate, lithium difluorooxalate borate, lithium tetrafluorooxalate phosphate, lithium difluorobisoxalate phosphate, and lithium fluorosulfonyl(trifluoromethylsulfonyl)imide, and the molar concentration of the electrolyte in the electrolytic solution is 0.5 to 2 mol / L.
5. The lithium ion battery electrolyte according to claim 4.
8. Use of the lithium ion battery electrolyte according to any one of claims 4 to 7, The lithium ion battery electrolyte is used in lithium ion batteries having lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminate, lithium nickel cobalt manganese aluminate, or lithium iron manganese phosphate as a positive electrode.
2. Use of a lithium-ion battery electrolyte.
9. The lithium ion battery electrolyte is used in lithium ion batteries with a carbon or silicon-based negative electrode.
9. Use according to claim 8.
Citation Information
Patent Citations
Electrolyte for lithium secondary battery and lithium secondary battery using it
JP2000195545A
Nonaqueous electrolytic solution and its secondary battery
JP2001256995A
Nonaqueous electrolyte and nonaqueous electrolyte secondary battery using the electrolyte
JP2002100402A
Nonaqueous electrolyte and nonaqueous electrolyte secondary battery using the electrolyte
JP2009193836A
Nonaqueous electrolyte and nonaqueous electrolyte secondary battery using the nonaqueous electrolyte
JP2010267509A